IMPLEMENTATION OF MOSQUE FUNCTIONS IN TELUK NIBUNG DISTRICT IN THE PERSPECTIVE OF WAHBAH AZ-ZUHAILI - Muhammad Jihad Azni Lubis; Mardian Idris Harahap (el-Umdah, 2023)
Abstract: Some of the Muslims understand that the function of the mosque is only for worship such as prayer and reading the Qur'an, even though the real function of the mosque is not only for that but there are many more functions. This study aims to explore the function of the mosque in the Qur'an, precisely surah An-Nur: 36-38 and take from Wahbah Az-zuhaili's perspective in tafsir Al-munir. This research is written using library research and field research methods, namely with books related to the discussion of research and researching directly in the field that has been determined. The result of this study is that it can be understood that it is very clear what the functions of the mosque are according to Wahbah Az-Zuhaili's perspective, namely the mosque functions as a place for the formation of aqidah, the mosque functions as a ray of guidance, the mosque functions as a place of worship, the mosque functions as a place of rest, the mosque functions as a place for managing community affairs, the mosque functions as a place for shaping behavior, the mosque functions as a place for education to study knowledge, and the mosque functions as a place to understand politics.